IODINE ABSORPTION BY APPLE LEAF SURFACES. Issue 13 (9th September 2022) - Yanai, Masumi; Kawabata, Hitoshi; Takaku, Yuichi
Abstract: Apple is an important agricultural product in Aomori Prefecture, Japan, where the first commercial nuclear fuel reprocessing plant is currently under construction. As the behavior of radioiodine deposited on the surface of apple leaves is not well known, we studied the absorption and transfer to fruit of stable iodine applied onto the leaf surface. Droplets of NaI solution were applied to the leaf surface $\sim$ 86–89 days after flowering. The leaves were collected periodically and washed with detergent solution, followed by determination of iodine amounts absorbed or remaining on the leaf surface. Subsequently, iodine levels were determined separately for each part of the apple tree. Our results indicated that iodine applied on the surface of the leaf was absorbed and accumulated inside the leaf, but the transfer of absorbed iodine to the fruit was negligible; hence, iodine was less likely to accumulate in the fruit.